Does the law prevent access to justice? (access to civil justice in the Malaysian courts) - Mohamed Abdullah, Abu Haniffa (2007)
This paper intends to explore some laws, rules of court and practices which restrict access to justice or deny justice or lead to miscarriage of justice using the common law adversary system in the Malaysian civil courts. The topics to be covered are couse of action, statues of limitation, restrictions on right of appeal, abuse of judicial discretion, restrictions arising from rules of pleadings, failures of the adversary system and public policy decisions although there are many more for which there is no space in this paper.